Associated factors with the self-care of people with diabetes mellitus in the COVID-19 pandemic - Bárbara Shibuya Alves; Odete de Oliveira Monteiro; Meiry Fernanda Pinto Okuno; Paula Cristina Pereira da Costa (Universidade Federal do Ceará, 2023)
Objective: to analyze the factors associated with self-care in people with diabetes during the COVID-19 pandemic. Methods: cross-sectional analytical and exploratory online study with 70 participants, using the Summary Diabetes Self-Care Activities Questionnaire. The clinical and sociodemographic profile was portrayed with a descriptive analysis. Fisher's exact test, the Chi-square test and Poisson regression with robust variance were used to determine the association between the variables. Results: after regression, the items Physical Activity, Use of Medication and General Diet from the Summary Diabetes Self-Care Activities Questionnaire showed, respectively, a significant association with the variables Physical Exercise (p<0.001), Occupation (p=0.005) and Age (p=0.01). Conclusion: the physical exercise, medication use and general diet items on the self-care questionnaire were related to the variables of age, occupation, and physical exercise, respectively. Contributions to practice: health services should intensify the investigation of factors associated with the difficulties of people with diabetes, to offer a better quality of life and adequate health promotion for this population.